Modern Digital Control - Gaofeng, Zhou; Qi, Zhang (Modern Control Systems: Theory, Design and Applications, 2025)
The theme in chapter 11 is modern digital control for modern digital control was a main trend and control fashion in the present industry. Basic conceptions were narrated and explained to understand modern digital control systems. Then stability and steady-state error were applied and analyzed and deduced. Beside these, transient response, gain and nonlinear state observer were also introduced to further analyze a digital control system given. Furthermore, some key elements and applications in digital control were narrated and enumerated.